Influencia de la Técnica de Dramatización de Títeres para mejorar la Comprensión Lectora en las niñas de segundo grado de Primaria de la I.E. Nº 81007 “Modelo”- Trujillo, 2016 - León Hilario, Esthefani Cristina (2017)
The present work entitled "Influence of the technique of puppet dramatization to improve reading comprehension in the girls of second grade of I.E Nº 81007" Model - Trujillo, 2016 "; Significantly influences the improvement of reading comprehension._x000D_ The study was carried out with a sample of 25 students enrolled in the 2nd grade of Elementary Education of Educational Institution N ° 81007 "MODELO", in the city of Trujillo, 2016. The type of applied research was used, using the quasi-perimetal design. As an instrument of data collection, a reading comprehension booklet was used_x000D_ The results allow us to confirm that students in the experimental group have improved significantly in Reading Comprehension, this is due to their participation in the learning sessions of the program. _x000D_ In conclusion the application of the "TECHNIQUE OF THE DRAMATIZATION OF PUPPETS". Has significantly influenced the development of reading comprehension levels (literal inferential, critical).